2003
DOI: 10.1046/j.1365-2389.2003.51305.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Prognostic Importance of Total Cholesterol in Elderly Survivors of an Acute Myocardial Infarction: The Cooperative Cardiovascular Pilot Project

Abstract: Among elderly survivors of AMI, elevated total serum cholesterol measured postinfarction is not associated with an increased risk of all-cause mortality in the 6 years after discharge. Furthermore, this study found no evidence of an increased risk of all-cause mortality in patients with low total cholesterol. Further studies are needed to determine the relationship of postinfarction lipid subfractions and mortality in older patients with coronary artery disease (CAD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Suggested markers for risk for all‐cause mortality include high resting heart rate and low serum albumin levels 9–12 . It has also been suggested that low serum cholesterol levels may be associated with adverse outcomes in this age group, but this association is still controversial 13–18 …”
mentioning
confidence: 99%
“…Suggested markers for risk for all‐cause mortality include high resting heart rate and low serum albumin levels 9–12 . It has also been suggested that low serum cholesterol levels may be associated with adverse outcomes in this age group, but this association is still controversial 13–18 …”
mentioning
confidence: 99%
“…Although recent studies have argued that “undertreatment” and “age bias” exist in the management of hyperlipidemia in patients aged 80 and older, 1 there is clinical uncertainty about the optimal approach in the very old. Although the lowering of low‐density lipoprotein cholesterol (LDL‐C) levels in younger patients with acute myocardial infarction (AMI) is known to reduce disease progression, 2 adverse events, and mortality, 3–8 data are lacking regarding the effect of treating hypercholesterolemia in patients aged 80 and older after AMI 9 . Few patients aged 80 and older have been enrolled in clinical trials, and those that have been enrolled may not be representative 10 .…”
mentioning
confidence: 99%
“…Although the lowering of low-density lipoprotein cholesterol (LDL-C) levels in younger patients with acute myocardial infarction (AMI) is known to reduce disease progression, 2 adverse events, and mortality, [3][4][5][6][7][8] data are lacking regarding the effect of treating hypercholesterolemia in patients aged 80 and older after AMI. 9 Few patients aged 80 and older have been enrolled in clinical trials, and those that have been enrolled may not be representative. 10 Accordingly, national guidelines support the aggressive use of lipid lowering in a wide range of patients younger than 80, but for those aged 80 and older, there are often reservations, 11 and physician discretion is advised.…”
mentioning
confidence: 99%
“…Prior studies suggested a weaker relationship among the elderly between serum cholesterol and the development of coronary artery disease. 17,18 Foody et al 19 recently published a long-term retrospective analysis of 4923 Medicare beneficiaries age 65 and older who were discharged with a principal diagnosis of AMI. 19 There was no significant difference in either the 1-year or 6-year unadjusted mortality between those with a cholesterol <240 mg/dL and those with a cholesterol level ≥240 mg/dL.…”
Section: Discussionmentioning
confidence: 99%